Analisis takdir Allah terhadap perbuatan manusia yang berlandaskan Al-Qur’an - Fayyahd, Muh (Maliki Interdisciplinary Journal, 2024)
Destiny includes all events that have happened, are happening, and will happen, all of which have been determined by Allah SWT. Whether things are good or bad, everything happens according to His plan and will. However, humans are given the right to try as hard as they can, while the final result is determined by Allah SWT. Fate is the decree of Allah SWT which covers all events in the universe, including their levels and sizes. This research is qualitative research that uses library research methods, namely research based on scientific papers and articles that have been published. From the results of the analysis, it was found that all human actions on this earth will receive a good destiny when their actions are good, but when the human's own actions are not considered good by the creator, then he will receive a destiny according to his own actions. So we as humans cannot determine or know what our destiny will be in the world, we as humans can only keep trying and praying, everything depends on Allah SWT. Who sees all human actions